“CATFISHING” : EXPOSING TEEN RECEPTION ON MTV CATFISH ONLINE DATING - Garini Tiara Senja; Santi Delliana (Faculty of Social Sciences and Humanities Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2022)
Advanced technology has made meeting new people less conventional than it used to be. The Internet has taken romance into a whole different world and created a whole different threat with the idea of online dating. Internet users are faced with many threats every day, but online dating has caused a threat with a form of online identity deception called catfishing. Catfishing itself is the theme of an MTV reality show named Catfish: The TV Show. This study aims to find out about the reaction of adolescent online daters on catfishing on the program. This descriptive qualitative study uses Stuart Hall's Reception Analysis method and its three hypothetical positions, such as Dominant-Hegemonic position, Negotiated position, and Oppositional position. Results show different readings on each of the six pieces of information given in the chosen episode. Four pieces of information such as when the client first reached out to Catfish: The TV Show team, the team investigated the catfish, the team to arrange a meeting with the catfish, and the meeting with the catfish are dominated by the Dominant-Hegemonic Position. Meanwhile, the rest of the two pieces of information are dominated by the Negotiated position and the Oppositional position.However, the complete study result is dominated by the Oppositional position.